PENGARUH LITERASI KEUANGAN TERHADAP PENGGUNAAN PRODUK PERBANKAN DI KALANGAN MAHASISWA - Salman Alfarisi; Zahra Ibna Afifah Yuliarti; Sultan Iskandar Surya Dinata; Moh. Alfian Syahada; Achmarul Fajar (Jurnal Riset Multidisiplin Edukasi, 2026)
Financial literacy is an individual's ability to understand, manage, and make appropriate financial decisions. A good level of financial literacy is an important factor in encouraging the use of banking products and services, especially among university students who are increasingly involved in various financial activities. This study aims to analyze the influence of financial literacy on the use of banking products among university students based on findings from previous studies. The method used in this research is a literature review, which examines various scientific journals, research articles, and relevant references related to financial literacy and the use of banking products. The findings indicate that financial literacy has a positive influence on the use of banking products. Students with a higher level of financial literacy tend to have a better understanding of the benefits, risks, and features of banking products, making them more likely to utilize services such as savings accounts, mobile banking, internet banking, deposits, and Islamic banking products. In addition, several supporting factors, including the accessibility of digital banking services, service quality, trust in banking institutions, religiosity, and promotional strategies implemented by banks, also influence students’ decisions to use banking products. Conversely, a low level of financial literacy may limit students’ ability to effectively utilize available banking services. Therefore, improving financial literacy through financial education, socialization programs, and financial learning initiatives is essential to enhance students’ understanding and utilization of banking products.